The Peran Kepala Sekolah dalam Manajemen Kurikulum di SMP Unggulan Roudhotul Huda Magetan - Sholehah, Fedelara Rizqiana Putri; Jihan, Tarissa Farah (LP. Ma'arif Janggan Magetan, 2024)
The school principal holds a crucial role in the implementation of educational institution program, particulary in curriculum management, where its important to understand the role and contribution of th principal. This study aims to explore how the principal take an important role in curriculum management. AT smp Roudlotul Huda, the principal’s responbilities include planning, organizing, implementation and evaluation process. This research adopts a qualitative method with descriptive and data analysis. The study seeks to identify the role of the principal at SMP Unggulan Roudlotul Huda, as a supervisor in insuring the effective curriculum management within the educational institution. The findings indicate that th e principal actively engages in all stage of curriculum management, from planning to evaluation.